2007
DOI: 10.1177/1460408607082845
|View full text |Cite
|
Sign up to set email alerts
|

Postconcussion syndrome: a review

Abstract: ResumenEl incremento de la tecnología se ha extendido en todas las áreas de la medicina, un cambio con relación al diagnóstico ha ocurrido también en los estudios de imagen. El síndrome de VOMIT significa "Víctima de la tecnología de imagen médica" (Victim of Modern Imaging Technology) y es un término utilizado para describir colectivamente los pronósticos adversos que tiene el diagnóstico, tratamiento o pronóstico del paciente politraumatizado debido a la mala aplicación o interpretación de estudios de imagen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 81 publications
(86 reference statements)
0
3
0
Order By: Relevance
“…complaints of post-concussive symptoms who have been referred, typically by the treating medical facility or sports team, for assessment to a neuropsychologist or to an out-patient clinic for treatment [4,18,24,[104][105][106][107][108][109]. These approaches have typically assessed persons in the acute post-injury period, perhaps because the literature regarding long-standing impairments in cognitive function and other domains following milder brain injuries has been highly controversial (refer to [16][17][18]102] for discussion). The inclusion criteria were much more broad (only 39% of the sample reported medical/formal documentation of his/her injury) and assessed subjects months post-injury (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…complaints of post-concussive symptoms who have been referred, typically by the treating medical facility or sports team, for assessment to a neuropsychologist or to an out-patient clinic for treatment [4,18,24,[104][105][106][107][108][109]. These approaches have typically assessed persons in the acute post-injury period, perhaps because the literature regarding long-standing impairments in cognitive function and other domains following milder brain injuries has been highly controversial (refer to [16][17][18]102] for discussion). The inclusion criteria were much more broad (only 39% of the sample reported medical/formal documentation of his/her injury) and assessed subjects months post-injury (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Although the severity of head trauma and/or neural disruption may be viewed on a continuum [2,15] ranging from mild-to-severe (MHI, concussion, post-concussive syndrome [PCS], MTBI, moderate-to-severe brain injury), the persistence of these changes for injuries at the milder end of the continuum of severity of injury has long been controversial and at times is still poorly understood [16][17][18][19][20][21]. Most often the research has suggested that symptoms following milder head traumas are most often resolved by 3 months [22,23]; however, there has been accumulating evidence to suggest that complaints or impairments following MHI or MTBI may not be transient for a sub-population of persons.…”
Section: Introductionmentioning
confidence: 99%
“…Su and colleagues report that elevated levels of CRP, which is indicative of systemic inflammation, at 1, 2, and 3 months after a mild TBI was significantly correlated with persistent neuropsychological symptoms 122 . Of particular note, the typical symptoms of sickness behavior following injections of LPS in models of experimental endotoxemia shares considerable overlap with a constellation of symptoms often referred "post-concussion syndrome (PCS)" 71,123,124 . In fact, Rathbone and colleagues recently made a compelling case to re-term PCS as "post-inflammatory brain syndrome"…”
Section: "Bottom-up": Potential Gut-to-brain Signalingmentioning
confidence: 99%